Anticipating the plot: overdetermining heteronormative destiny on the twenty-first century screen. Issue 3 (4th March 2023) - Pellegrini, Chiara
ABSTRACT: This article examines narrative temporalities in three texts – the Hollywood romantic film The Time Traveler's Wife (2009), the nine-season sitcom How I Met Your Mother (2005–2014) and the reality television show Love is Blind (2020-) – in order to show how formal choices such as editing, voiceover narration and event selection reveal an investment in heteronormative ideals. These narratives foreground time in a way that is specific to their medium, all achieving a tension between securing heterosexual marriage and reproduction in their characters' futures and threatening to jeopardise these very endings. However, the more the resolution becomes certain, be it through prolepsis by a retrospective narrator, literal visits to the future in the storyworld or the contrivances of reality television, the more the participants in the narrative appear 'trapped' in a preordained timeline, in ways that resonate with how subjects exist in relation to ideologically dominant modes of living. Using Judith Roof's argument about the metaphorical heterosexuality of narrative form, Mark Currie's notion of depresentification and Sarah Ahmed's analysis of 'happy objects', the article argues that repeated anticipations of a predetermined heteronormative ending undermine, rather than reinforcing, the desirability of the goals that the characters are striving to reach.